Semantic Mapping Strategy to Improve Students' Writing Skill - Albadri Albadri (JOEY: Journal of English Ibrahimy, 2022)
Semantic Mapping is a simple strategy used by students by clustering words starting with determining the main idea according to the theme they will tell and supported by words related to the main idea. this study aims to (1) The influence of semantic mapping strategy on students' ability to write recount text (2) to test the effectiveness of the semantic mapping strategy of students' ability to write recount text. The method used in this research is a Quasi-Experimental method with a Non-equivalent design. Data obtained through tests and documentation. The sample of this research was 15 students of Elementary. based on the results of the pre-test and post-test, students' ability in writing recount texts increased by 38, which is the difference between the control class' post-test average score of 48 and the experimental class's post-test average score of 86. Furthermore, based on the statistical calculation of 0.05, the value of Sig. < 0.05 (0.045 < 0.05), means that the use of the Semantic Mapping strategy is effective in improving the ability to write recount text.